2023
DOI: 10.3389/fonc.2022.1101830
|View full text |Cite
|
Sign up to set email alerts
|

The different predictive value of mean platelet volume-to-lymphocyte ratio for postoperative recurrence between non-muscular invasive bladder cancer patients treated with intravesical chemotherapy and intravesical chemohyperthermia

Abstract: IntroductionThe inflammatory response plays a potential role in postoperative recurrence in patients with non-muscular invasive bladder cancer (NMIBC). We aimed to investigate whether platelet-to-lymphocyte ratio (PLR), mean platelet volume to lymphocyte ratio (MPVLR), and the systemic immune-inflammatory index (SII) have prognostic values in NMIBC treated with conventional intravesical chemotherapy or intravesical Chemohyperthermia (CHT) and the differences between them.Materials and methodsA retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additionally, various growth factors such as TGF-β and PDGF are released by platelets and promote tumor growth by promoting angiogenesis, inducing the expression of tissue factors and other ways ( Tesfamariam, 2016 ; Saito et al, 2018 ). In BLCA, scientists have found that the platelet-to-lymphocyte ratio has the potential to predict the efficacy of various therapies ( Zhang et al, 2015 ; Wang et al, 2022 ; Wu et al, 2022 ). The diagnosis and prognosis predicting values of hemoglobin-to-platelet ratio, platelet-to-leukocyte, platelet volume and platelet distribution width have been also explored in BLCA ( Schulz et al, 2017 ; Tang et al, 2018 ; Song et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, various growth factors such as TGF-β and PDGF are released by platelets and promote tumor growth by promoting angiogenesis, inducing the expression of tissue factors and other ways ( Tesfamariam, 2016 ; Saito et al, 2018 ). In BLCA, scientists have found that the platelet-to-lymphocyte ratio has the potential to predict the efficacy of various therapies ( Zhang et al, 2015 ; Wang et al, 2022 ; Wu et al, 2022 ). The diagnosis and prognosis predicting values of hemoglobin-to-platelet ratio, platelet-to-leukocyte, platelet volume and platelet distribution width have been also explored in BLCA ( Schulz et al, 2017 ; Tang et al, 2018 ; Song et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also identified that the mutation of ZFHX3 in NSCLC patients could have benefit from ICIs treatment (Principe, 2022). ZFHX3 was identified as a genomic mutation for prediction of immunotherapy in NSCLC patients (Wang Z. et al, 2022). ZFHX3 mutation in NSCLC patients was correlated with TILs, immune-related gene expression and tumor mutation burden.…”
Section: The Efficacy Of Immunotherapy In Zfhx3mutant Nsclcmentioning
confidence: 96%